2007
DOI: 10.3892/ijmm.19.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and variations in core promoter and pre-core regions are related to progression of disease in HBV-infected patients from Northern Vietnam

Abstract: Abstract.Vietnam is one of the countries with a high rate of hepatitis B virus (HBV) infection, but there are only a few reports about relation of HBV genotypes and mutations to clinical course in Northern Vietnam. The characteristics of HBV and its relationship to clinical outcome in patients from Northern Vietnam were analyzed. Serum samples were collected from 183 HBV-infected Vietnamese patients. They were clinically categorized into 4 groups: hepatocellular carcinoma (HCC), liver cirrhosis (LC), chronic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
5
11
0
Order By: Relevance
“…31 Our result was similar to previous studies conducted in Vietnam that indicated that HBV genotype B was the most prevalent (63.0%-72.6%) followed by genotype C (18.0%-28.0%). [32][33][34][35] Like other studies, 5,6,23,24,28,36 our results also showed no statistically significant association between possible occupational risk factors for HBV infection among beauticians. However, some studies have suggested that beauticians are a high-risk group for HBV and HCV infections based on the statistically significant difference in prevalence among case and control groups, 24,36,37 or by comparing HBV infected cases with HAV infected cases as a control group.…”
Section: Discussionsupporting
confidence: 64%
“…31 Our result was similar to previous studies conducted in Vietnam that indicated that HBV genotype B was the most prevalent (63.0%-72.6%) followed by genotype C (18.0%-28.0%). [32][33][34][35] Like other studies, 5,6,23,24,28,36 our results also showed no statistically significant association between possible occupational risk factors for HBV infection among beauticians. However, some studies have suggested that beauticians are a high-risk group for HBV and HCV infections based on the statistically significant difference in prevalence among case and control groups, 24,36,37 or by comparing HBV infected cases with HAV infected cases as a control group.…”
Section: Discussionsupporting
confidence: 64%
“…Each subgenotype has a unique geographic distribution and virological characteristics. Vietnam is one of the most endemic areas of HBV infection, and the prevalence of HBV subgenotypes in patients with chronic hepatitis in Vietnam has been reported [5][6][7][8] . HBV subgenotypes C1 and B4 are frequently found in Vietnam.…”
mentioning
confidence: 99%
“…22 In China, genotypes B and C are the two most commonly found genotypes, that contributing 90% of the population of chronic hepatitis B patients. The clinical importance of genotype related differences in CHB patients remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%